Parliamentary session turned into political poetry (Revista de Estudios Brasileños, 2018)
This review analyzes the poetry book Session (Luna Park, 2017). In the book, author Roy David Frankel selects some of the speeches given by congressmen during the session of the Chamber of Deputies – one of the two chambers of the Brazilian parliament – that authorized the trial of the elected president Dilma Rousseff due to “crime of responsibility” (a process known as impeachment) and turns each speech into a poem. For this, the author maintains the integrality of each discourse, but reorganizes them into free verses, broadly using the enjambment and other creative formal resources to transform into powerful political poetry the traumatic episode that took place in Brazil in 2016.